Is The Agricultural Sector Cursed Too? Evidence From Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
Extractive and agricultural resources do not have the same impact on poverty reduction and can compete with each other. We examine how extractive resource windfalls affect agricultural productivity, measured as the amount of output per worker in the agricultural sector. This is important since agricultural productivity is a key element of structural transformation and poverty reduction. To do this, we exploit a panel dataset of 38 countries over 1991-2016 and construct a country-specific commodity price index that captures resource-related gains and losses in aggregate disposable income. We find that an increase in the commodity price index leads to a drop in agricultural productivity in Sub-Saharan economies. Among the possible mechanisms to explain this result, our findings highlight the lack of spillovers across sectors and the low level of agricultural investment in autocratic regimes, both related to the exploitation of extractive resources. We also find that higher agricultural productivity is positively associated with the release of workers towards manufacturing and services, confirming its importance for structural transformation.
Keywords: African Research